The GAy MEn Sex StudieS: Anodyspareunia Among Belgian Gay Men. Issue 2 (15th August 2013) - Vansintejan, Johan; Vandevoorde, Jan; Devroey, Dirk
Abstract Introduction Anal intercourse is commonly associated with male homosexuality, but not all gay males engage in anal sex. Receptive anal intercourse can cause pain. Little is known about this sexual dysfunction. Aim This study aims to determine the 4‐week incidence of anodyspareunia (AD) in a sample of Belgian men who have sex with men (MSM) population and to assess the relevance of possible predictors such as age, relationship, and sexual behavior. Methods An internet‐based survey on sexual behavior and sexual dysfunctions, called GAy MEn Sex StudieS, was administered to the MSM aged 18 years or older, between April and December 2008. A part of the questionnaire was focusing on anal eroticism. The participants, who self‐reported being human immunodeficiency virus‐positive or not having anal intercourse, were excluded. Main Outcome Measure Female Sexual Function Index questions on pain domain adapted for anal intercourse. Results A total of 1, 752 Belgian MSM completed the questionnaire. Of the 1, 190 (68%) participants who reported engaging in receptive anal sex in the last 4 weeks, 59% indicated having some degree of anal pain during and after sexual intercourse. For 44%, the level of pain was acceptable. Mild AD was reported by 32%, 17% had mild to moderate AD, 4% had moderate AD, and 2% had severe AD. Independent predictors for the presence of AD were age, having a steady relationship, frequency of sex with their partner, number of sex partners, number of sex partners at the same time, and massaging the anal sphincter before anal sex. The prevalence and severity of AD among the MSM were lower among older participants, the MSM who more frequently had sex with their partner, and participants with a higher number of sex partners. Inadequate lubrication and lack of oral or digitoproctic stimulation prior to penetration were the most important factors predicting pain. Unsafe anal sex was performed by 28%. Conclusion One‐third of the participants reported not engaging in receptive nor penetrative anal sex. The 59% of participating Belgian MSM, who had anal receptive intercourse, reported some degree of AD. These findings highlight the need for more education about anal eroticism for MSM, and more research into AD is needed. Vansintejan J, Vandevoorde J, and Devroey D. The GAy MEn Sex StudieS: Anodyspareunia among Belgian gay men. Sex Med 2013;1:87–94.